PEMBUKTIAN UNSUR PATUT DIDUGA PADA DELIK PENADAHAN KENDARAAN BERMOTOR DALAM PUTUSAN PENGADILAN NEGERI MALANG NOMOR 123/Pid.B/2017/PN.MLG - Wahyu Jati Kuncoro; R Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2021)
Criminal Offense in Indonesia have been clearly regulated in Article 480 of the Criminal Code, where a person is declared as an intermediary if he has fulfilled the elements contained in Article 480 of the Criminal Code, The elements in this article are where he rents, buys, receives as a gift, accepts a pledge, accepts an exchange, or because he wants to earn a profit from selling, mortgaging, exchanging, hiding, storing, or carrying goods that he knows, where the elements contained in the article are: The emphasis is on the recipient or buyer of the goods who must be considered as supposed to know and reasonably suspect that the goods to be purchased or received are goods obtained through the proceeds of crime. The problem faced is how to prove the suspected element in the offense of arresting a motor vehicle in the Malang District Court Decision Number 123/Pid.B/2017/PN.Mlg. The research method used is normative juridical. The results of the study indicate that the elements contained in the article focus on the recipient or buyer of the goods who should be considered as supposed to know and reasonably suspect that the goods to be purchased or received are goods obtained through the proceeds of crime. Therefore, the public is required to always be vigilant and should be suspicious and be more careful in obtaining or buying an item, first check the item, that the item is of clear origin and is not obtained from the proceeds of a crime.